Intersubunit communication in glycogen phosphorylase influences substrate recognition at the catalytic sites - Nahori Kamada; Ayato Ikeda; Yasushi Makino; Hiroshi Matsubara (Amino Acids)
Abstract Glycogen phosphorylase (GP) is biologically active as a dimer of identical subunits, each activated by phosphorylation of the serine-14 residue. GP exists in three interconvertible forms, namely GPa (di-phosphorylated form), GPab (mono-phosphorylated form), and GPb (non-phosphorylated form); however, information on GPab remains scarce. Given the prevailing view that the two GP subunits collaboratively determine their catalytic characteristics, it is essential to conduct GPab characterization to gain a comprehensive understanding of glycogenolysis regulation. Thus, in the present study, we prepared rabbit muscle GPab from GPb, using phosphorylase kinase as the catalyst, and identified it using a nonradioactive phosphate-affinity gel electrophoresis method. Compared with the half-half GPa/GPb mixture, the as-prepared GPab showed a unique AMP-binding affinity. To further investigate the intersubunit communication in GP, its catalytic site was probed using pyridylaminated-maltohexaose (a maltooligosaccharide-based substrate comprising the essential dextrin structure for GP; abbreviated as PA-0) and a series of specifically modified PA-0 derivatives (substrate analogs lacking part of the essential dextrin structure). By comparing the initial reaction rates toward the PA-0 derivative (V derivative) and PA-0 (V PA-0), we demonstrated that the V derivative/V PA-0 ratio for GPab was significantly different from that for the half-half GPa/GPb mixture. This result indicates that the interaction between the two GP subunits significantly influences substrate recognition at the catalytic sites, thereby providing GPab its unique substrate recognition profile.